Optimization of the bremsstrahlung converter - Rudychev, V.G.; Azarenkov, M.O.; Girka, I.O.; Lazurik, V.T.; Rudychev, Y.V. (Вопросы атомной науки и техники, 2022)
Variants of the formation of bremsstrahlung (BS) distributions along an extended converter, which ensures the maximum thickness of an object under two-sided and four-sided irradiation, are studied. For the target of the TaH₂OFe converter, the thicknesses of the Pb filter were determined, at which the average BS energy increases by more than 25%. In the PENELOPE package, the simulation of dose distributions in polyethylene produced by BS converters with optimal targets: previously used TaH₂OFe and proposed by us TaH₂OFePb, for 7.5 MeV electron energy, was performed. For four-sided irradiation, a technique for optimizing the distribution of the BS intensity along an extended converter is proposed. The combined use of the TaH₂OFePb target and optimal BS intensity distributions along an extended converter makes it possible to increase the thickness of objects by a factor of ~ 1.35 under four-sided irradiation, DUR < 1.5. Досліджено варіанти формування розподілів гальмівного випромінювання (ГВ) вздовж протяжного конвертера, що забезпечує максимальну товщину об’єкта при двосторонньому та чотиристоронньому опроміненні. Для мішені конвертера TaH₂OFe визначено товщини фільтра з Pb, при яких середня енергія ГВ зростає більш, ніж на 25%. У пакеті PENELOPE виконано моделювання дозових розподілів у поліетилені створюваних ГВ конвертерами з оптимальними мішенями: раніше використовуваним TaH₂OFe та запропонованим нами TaH₂OFePb, енергія електронів 7,5 МеВ. Для чотиристороннього опромінення запропоновано методику оптимізації розподілу інтенсивності ГВ вздовж протяжного конвертера. Комбіноване використання мішені TaH₂OFePb та оптимальних розподілів інтенсивностей ГВ вздовж протяжного конвертера дозволяє збільшити у ~ 1.35 рази товщину об’єктів при чотиристоронньому опроміненні, DUR < 1,5.